Patient-reported gastrointestinal symptoms in gastric cancer after laparoscopic distal gastrectomy - Xiao, Shuomeng; Ding, Zhi; Zhao, Fazhi; Yang, Chao; Zhao, Ping; Chen, Xiaodong; Zhou, Xiang; Zhou, Huali (Frontiers in Oncology, 2024)
PurposeThis study aimed to compare postoperative gastrointestinal symptoms between patients who underwent laparoscopic distal gastrectomy with Roux-en-Y (R-Y) and Billroth-II with Braun (B-II B) reconstruction.MethodsThis observational study retrospectively analyzed 151 patients (110 in R-Y group and 41 in B-II B group) who underwent laparoscopic distal gastrectomy from January 2020 to December 2021. A comparison was made regarding surgical outcomes, perioperative nutritional and inflammatory markers, postoperative dietary patterns, and gastrointestinal symptoms between the two groups.ResultsThe operation time was longer in the R-Y group than the B-II B group (261.00 ± 56.17 min versus 239.88 ± 57.78 min, p = 0.046). However, there were no significant differences in the length of hospital stay, ASA classification, complications, nutritional and inflammatory indexes, or recovery of postoperative diet between the two groups. Additionally, there were no significant differences in the occurrence of postoperative gastrointestinal symptoms in the post-discharge week (PDW) 1 and postoperative month (POM) 1 between the B-II B and R-Y groups.ConclusionsAbdominal distention emerged as the main gastrointestinal symptom burden in patients with gastric cancer undergoing laparoscopic distal gastrectomy. Both Billroth-II with Braun and R-Y reconstructions exhibited a high and similar incidence of gastrointestinal symptoms in the short term. Therefore, medical staff should pay attention to the management of gastrointestinal symptoms in these patients postoperatively.